Role of Capital Structure in Firm’s Value: A Case of Pakistani Firms - MUHAMMAD ASIF; MUHAMMAD USMAN HAMEED; ZAINULLAH KHALIL (Journal of Business & Tourism, 2021)
The Most important and critical decision for a finance manager is adequate Capital structure. Modigliani and Miller had started the debate of capital structure in creating firm’s value. The research was conducted to find out the impact of capital structure and the value of the firm in Pakistan. The research was conducted on 71 non-financial firms of KSE 100 index. Using fix effect regression in the study it was found that there is significant effect of Capital structure on firm’s value but the use of debt financing had negative relationship with the firm’s value.